2018
DOI: 10.1002/jcb.26529
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9‐mediated knockout of Lim‐domain only four retards organ of Corti cell growth

Abstract: Lim-domain only 4 (LMO4) plays a critical role in mediating the ototoxic side-effects of cisplatin, a highly effective anti-cancer drug. However, the signaling mechanism by which cochlear LMO4 mediates otopathology is yet to be fully understood. Knockout cell culture models are useful tools for investigating the functional roles of novel genes and delineating associated signaling pathways. Therefore, LMO4 knockout organ of Corti cells were generated by using the CRISPR (clustered regularly interspersed short p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In particular, CRISPR/Cas9 has been successfully applied to the creation of new in vitro and in vivo models of cochlear diseases [31]. For instance, this technology has allowed the study of genes associated with ototoxicity via the knock-out of Lim-domain only 4 (LMO4), for cisplatin, and HtrA Serine Peptidase 2 (htra2), for aminoglycosides, in vitro and in vivo models, respectively [32,33]. It has also allowed the study of inherited hearing loss genes, such as MYO7A, CIB2, and CDH23, for Usher syndrome [31].…”
Section: New Models Created By Crispr/cas9 Technologymentioning
confidence: 99%
“…In particular, CRISPR/Cas9 has been successfully applied to the creation of new in vitro and in vivo models of cochlear diseases [31]. For instance, this technology has allowed the study of genes associated with ototoxicity via the knock-out of Lim-domain only 4 (LMO4), for cisplatin, and HtrA Serine Peptidase 2 (htra2), for aminoglycosides, in vitro and in vivo models, respectively [32,33]. It has also allowed the study of inherited hearing loss genes, such as MYO7A, CIB2, and CDH23, for Usher syndrome [31].…”
Section: New Models Created By Crispr/cas9 Technologymentioning
confidence: 99%
“…In humans, LMO4 is known for its association with breast neoplasia and other types of carcinoma [9,[35][36][37]. Apart from a series of studies by Jamesdaniel and colleagues, which demonstrated that LMO4 and its downstream targets mediate the ototoxic effects of the commonly used anti-neoplastic agent cisplatin [13,14,16,17,40], its role in overall embryonic and inner ear development has not been a particular focus of clinical attention However, the possibility that Lmo4 serves as a regulator of Bmps (Figure 6B) or that Lmo4 and Bmps are involved in two parallel signaling pathways with mutual regulatory interactions (Figure 6C) cannot be ruled out.…”
Section: Clinical Significance Of Lmo4mentioning
confidence: 99%
“…Targeted disruption of Lmo4 in the mouse model led to dysmorphogenesis of the vestibule and negative regulation of sensory organ formation in the mammalian cochlea [11,12]. In addition to its role in inner ear development, recent research has revealed that Lmo4 and its downstream proteins play vital roles in mediating the ototoxicity of cisplatin, including cochlear apoptosis and hearing loss [13][14][15][16][17][18]. Lmo4 is proposed to act under the regulation of Bmp4 [19], with more recent evidence showing that Bmp2 regulates Lmo4 via an intermediate gene, Ntn1 [20].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, CRISPR/Cas9 has been successfully applied for creating new in vitro and in vivo models of cochlear diseases [30]. For instance, this technology has allowed to study genes associated with ototoxicity, via the knock-out of Lim-domain only 4 (LMO4), for cisplatin, and HtrA Serine Peptidase 2 (htra2), for aminoglycosides, in in vitro and in vivo models respectively [31,32]. It also allowed the study of inherited hearing loss genes, such as MYO7A, CIB2 and CDH23, for the Usher syndrome [30].…”
Section: New Models Created By Crispr/cas9 Technologymentioning
confidence: 99%